1999
DOI: 10.1161/01.cir.100.20.2093
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1A Receptor Knockout Mice Display Less Left Ventricular Remodeling and Improved Survival After Myocardial Infarction

Abstract: These results indicate that AT(1A) signals play a pivotal role in the progression of LV remodeling after MI, resulting in overt heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
142
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(151 citation statements)
references
References 37 publications
(40 reference statements)
6
142
1
2
Order By: Relevance
“…On the other hand, late remodeling progresses 1 to 2 months after MI, involving LV dilation, myocyte hypertrophy, and interstitial fibrosis. 3,21,22 In the present study, an interstitial fibrosis, which characterizes the late remodeling, was not evident either in Agtr2ϩ or Agtr2-mice, supporting that the process of the late LV remodeling had not started in these mice. In fact, the interstitial fibrosis developed in the 4th week after MI, the extent of which was significantly larger in Agtr2-mice than in Agtr2ϩ mice (data not shown).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…On the other hand, late remodeling progresses 1 to 2 months after MI, involving LV dilation, myocyte hypertrophy, and interstitial fibrosis. 3,21,22 In the present study, an interstitial fibrosis, which characterizes the late remodeling, was not evident either in Agtr2ϩ or Agtr2-mice, supporting that the process of the late LV remodeling had not started in these mice. In fact, the interstitial fibrosis developed in the 4th week after MI, the extent of which was significantly larger in Agtr2-mice than in Agtr2ϩ mice (data not shown).…”
Section: Discussionsupporting
confidence: 62%
“…6 It has been suggested that AT1R signaling mediates vasoconstriction, aldosterone secretion, cardiomyocyte hypertrophy, proliferation of fibroblasts, interstitial collagen deposition, and catecholamine release, all of which are implicated in progression of LV remodeling. 7,8 Harada et al 3 recently reported that AT1R gene-knockout mice had less LV remodeling and improved survival after MI. A deletion of AT1R or a blockade of AT1R with specific antagonists may result in selective binding of Ang II to the AT2R, indicating that the effect of AT1R blockade could be in part mediated by the effect of AT2R.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…G q activity has been inhibited in transgenic mice by overexpression of the carboxyl-terminal peptide of G ␣q ; inhibitor-expressing transgenic mice have a reduced hypertrophic response to aortic constriction (12), demonstrating that G q activation is necessary for this hypertrophic response. Overexpression and knockout of the AT 1 receptor produce phenotypes that are consistent with the G q data (13,14 (18). These data raise some interesting questions.…”
supporting
confidence: 71%
“…17,18 Our data suggest that iron deposition may exacerbate the cardiac fibrosis induced by angiotensin II. The findings that the myocardial fibrosis that occurs after myocardial ischemia can be attenuated by angiotensin-converting enzyme inhibitor and angiotensin receptor antagonist 19 and that less cardiac fibrosis is observed in the AT 1 receptor knockout mouse than in wild-type 20 suggest that angiotensin II has a crucial role in the development of cardiac fibrosis. Several factors that possibly mediate the fibrogenic effects of angiotensin II have been reported, such as transforming growth factor-␤ and cardiac aldosterone.…”
Section: Discussionmentioning
confidence: 99%